Aprovechamiento de los residuos orgánicos de plazas de mercado, manejo de podas y lodos de la Planta de Tratamiento de Agua Residual Doméstica generados en el casco urbano del municipio de Guachené (2019)
In this work the physicochemical characteristics of the residues of the market place, sludge of the sewage treatment plant and pruning residues of the municipality of Guachené of the department of Cauca were analyzed. According to the characterization of the municipal solid waste, it was found that the waste in the market place is generated in greater proportion, with a monthly quantity of 326.08 kg, followed by PTAR sludge with 135.47 kg, and finally the pruning residues that generate every month 61.8 kg. The results of the elementary analysis of the residues showed that the residues of market place have a greater potential to generate methane individually; however, in all cases it is always important to keep in mind the amount of waste to be used; that is, as the elementary analysis of the waste showed that for the solid waste of market places 0.35 m3 of CH4 can be obtained per 1.0 kg of waste, for PTAR sludges 0.14 m3 of CH4 can be obtained per 1.0 kg of sludge and for pruning residues 0.29 m3 of CH4 can be obtained per 1.0 kg of treated pruning. Based on the analysis of the general context of the municipality, a strategy was formulated for the exploitation of the residues, using the anaerobic digestion of the residues by means of an anaerobic digester , where it was obtained as market place residues can present a methane production around 0.98 m3 CH4 /day, pruning of 0.77 m3 CH4 /day and PTAR sludge a production of 0.13 m3 CH4 /day. Finally it was found that when performing a Co-digestion of the residues the production of methane is 4.33 m3 CH4 /day, which indicates that the production increases if the mixture of the residues is performed, allowing the conclusion that the waste management strategy of the municipality of Guachené, can represent a significant reduction of the problems associated with solid waste management in the municipality and the costs associated with the operation, transport and final disposal of waste